Growth and Development of Islamic Kingdoms in Java - Basri, Muhammad; Pitriana, Eka Riski; Hasibuan, Yuli Anisah (Lembaga Riset Mutiara Akbar, 2024)
Islam is the most common religion of the Indonesian populace. The function of scholars and Muslims in Indonesia is inextricably linked to the introduction of Islam. merchants in the formation of several Indonesian kingdoms that practice Islam. We discovered evidence of the expansion of Islam throughout the nation, one of which is the various traces of the Islamic kingdom of Indonesia, especially those found in the Javanese islands. This research discusses the process of growth and development of Islamic kingdoms in Java in certain historical periods. Through analysis of historical sources, this research reveals the factors that influenced political and religious conversion in the region. The role of ulama, trade and cultural interactions between Islamic kingdoms in Java are the main focus in understanding social and political changes. It is hoped that the results of this research will provide further insight into the dynamics of the history of Islam in Java. In this context, the spread of Islam in Java is not only limited to the religious aspect, but also includes the transformation of political institutions and social systems. This research documents how local authorities adopted Islamic teachings as the basis for legitimizing power, as well as how social norms changed over time.